A Broadly Cross-protective Vaccine Presenting the Neighboring Epitopes within the VP1 GH Loop and VP2 EF Loop of Enterovirus 71 - Xu, Longfa (Sci Rep, 2015)
Human enterovirus 71 (EV71) and coxsackievirus A16 (CA16) are the major etiological agents of hand, foot and mouth disease (HFMD) and are often associated with neurological complications. Currently, several vaccine types are being developed for EV71 and CA16. In this study, we constructed a bivalent chimeric virus-like particle (VLP) presenting the VP1 (aa208-222) and VP2 (aa141-155) epitopes of EV71 using hepatitis B virus core protein (HBc) as a carrier, designated HBc-E1/2. Immunization with the chimeric VLPs HBc-E1/2 induced higher IgG titers and neutralization titers against EV71 and CA16 in vitro than immunization with only one epitope incorporated into HBc. Importantly, passive immunization with the recombinant HBc-E2 particles protected neonatal mice against lethal EV71 and CA16 infections. We demonstrate that anti-VP2 (aa141-155) sera bound authentic CA16 viral particles, whereas anti-VP1 (aa208-222) sera could not. Moreover, the anti-VP2 (aa141-155) antibodies inhibited the binding of human serum to virions, which demonstrated that the VP2 epitope is immunodominant between EV71 and CA16. These results illustrated that the chimeric VLP HBc-E1/2 is a promising candidate for a broad-spectrum HFMD vaccine, and also reveals mechanisms of protection by the neighboring linear epitopes of the VP1 GH and VP2 EF loops.